Knowledge, Attitude, and Practice (KAP) of Radiographic Protection by Dental Undergraduate and Endodontic Postgraduate Students, General Practitioners, and Endodontists - Amal A. Almohaimede; Mohammad W. Bendahmash; Feras M. Dhafr; Abdullah F. Awwad; Ebtissam M. Al-Madi (Hindawi Limited, 2020)
The aim of this study is to evaluate the knowledge, attitude, and perception of radiation hazard and preventive measures among dental undergraduate students, general practitioners, endodontic postgraduate students, and endodontists in Saudi Arabia. Multiple choice questions questionnaires were distributed among undergraduate and endodontic postgraduate dental students, general practitioners, and endodontists in the colleges of dentistry in Saudi Arabia, government hospitals, and private clinics. The questionnaire included sociodemographic data, assessment of the knowledge of radiation physics and biology, assessment of the practice of dental radiography, and assessment of knowledge of radiation protection. Chi-square test was used for individual and multiresponse analysis. Level of statistical significance was set at P≤0.05. Three hundred and twenty-nine responded to the questionnaire. More than half of the respondents agreed that dental X-ray is hazardous to health (60.79%), and 68.1% were familiar with ALARA (as low as reasonably achievable) principle. However, only 34% are familiar with the recommendations of the National Council on Radiation Protection (NCRP) and International Commission on Radiological Protection (ICRP). The use of lead apron and thyroid collar for patients' protection from X-ray radiation was practiced among endodontic postgraduate students more frequently as well as those who are proactive in the academic field. Undergraduate students, endodontic postgraduate students, and endodontists in the academic field were the most aware towards radiation reduction measures. The use of the preventive measures needs to be emphasized more among general practitioners, endodontic postgraduate students, and endodontists especially in governmental hospitals and private sectors.